Perceptions of the role played by aquaculture and the services it provides for territories: complementarity of survey types - Mathé, S.; Rey Valette, H. (Scientific Research Publishing, Inc., 2018)
This article discusses the perception of ecosystem services for French and Brazilian pond fish farming. Its aim is to study the extent to which the industry and its stakeholders are aware of the existence of such services in order to be able to prioritize them with respect to social well-being. This identification phase is seldom discussed. It requires that survey questionnaires be designed so as to improve understanding of these perceptions. The surveys undertaken combined both open questions where the interviewees expressed their perceptions spontaneously and closed questions where they were invited to rank a pre-established list of the relevant services. These surveys involved 133 fish farmers and 93 stakeholders. The results show that perceptions differ by question type, and confirm the significance of the questionnaire design and the importance of combining several kinds of approach.